Expression levels of serum mir-145-5p and Gas6 in women with early-onset preeclampsia and their clinical significance - Huang, Ying; Zhang, Yanmei; Zhang, Li (Cellular and Molecular Biology, 2022)
Early preeclampsia is a pregnancy-specific clinical disease, its pathogenesis is not clear, and clinical treatment is limited. Therefore, it is particularly important to study the pathogenesis of early preeclampsia, so as to provide evidence for the diagnosis and effective treatment of early preeclampsia. This research was carried out to investigate the expression levels and clinical significance of mir-145-5p and stagflation specific gene 6 (Gas6) in serum of women with early preeclampsia. For this purpose, 142 patients with preeclampsia were divided into the early-onset group (n=78) and the late-onset group (n=64) according to the onset time. Meanwhile, 70 normal pregnant women were selected as the control group. The levels of serum Gas6, mir-145-5p and inflammatory factors were detected. Logistic regression analysis showed that the expression levels of serum gas-6 and serum mir-145-5p were valuable in the diagnosis of early preeclampsia. ROC curve was established to evaluate the diagnostic efficacy of serum Gas6 level in early-onset preeclampsia. Its sensitivity and specificity were 91.23% and 64.2%, respectively, and the cutting value was 255.71pg/mL. The serum Gas6 level was negatively correlated with systolic blood pressure (r=-0.349, P<0.05) and positively correlated with platelet count (r=0.391, P<0.05). Compared with the control group, serum levels of mir-145-5p and TNF-a in women with early-onset preeclampsia were negatively correlated (r=-0.460~0.622, P<0.05). Conclusion: the serum level of Gas6 was reduced in patients with early-onset preeclampsia, and TNF-a inhibited the invasion of SVneo cells by upregulating mir-145-5p.